Selected Determinants of Pronunciation Anxiety - Baran-Łucarz, Małgorzata; Lee, Jang Ho (International Journal of English Studies, 2021)
Empirical research shows that language anxiety has a detrimental effect on foreign language learning and its use. Several studies suggest that anxiety related to mastering and using foreign languages is skill-specific. This study examined pronunciation anxiety and attempted to determine its significant correlates. The included factors ranged from learning experiences with native-speaking teachers, previous studying abroad experience, and enjoyment of learning the target language, to willingness to communicate in the target language. A questionnaire was administered to two groups of EFL learners of different majors and different self-perceived levels. Hierarchical multiple regression analyses for both groups showed that willingness to communicate in English was the strongest determinant of pronunciation anxiety, while foreign language enjoyment the second meaningful correlate, but only in the case of the group whose self-assessment of general proficiency in English was lower.